The Effect of Unemployment and Inflation on Economic Growth in Aceh Province - Lutfi Multazam Khaironi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2021)
This study aims to see whether unemployment affects economic growth in Aceh Province, and whether inflation affects economic growth in Aceh Province. This study uses a multiple regression method whose data are taken from 1988-2017 per year. For data processing the author uses IMB SPSS statistics 16.0. The results showed that unemployment had a significant effect on economic growth, while inflation had no significant effect on economic growth. Researchers hope that the government should make or encourage entrepreneurs to increase their production. And also improve the payroll system and wage rates, as well as monitor prices and at the same time set maximum prices.